The Effect of Managerial Talented on Work Experience in Post Office Managers in Regional IV Jakarta - Agung Surya Dwianto; Pupung Purnamasari ((JEMS) Jurnal Entrepreneur dan Manajemen Sains, 2022)
Along with the Industrial Revolution, and now even entering the 5.0 Industrial Revolution, of course high creativity and innovation are required from each business entity. Organizations can no longer run a business as usual, every time and every time they are required to make various kinds of breakthroughs, so that they can remain relevant / survive the changes that occur. Likewise with what happened in the field of courier services, the industry in which PT. Pos Indonesia, whose conditions are currently getting tighter and fiercer. For this reason, a manager who has high work experience is needed in order to help the company win the existing competition. One way to get managers who have high work experience is to attract individuals who have good managerial talent to join the company. Managers who have good managerial skills tend to have high work experience, because these employees will always be prioritized when there is an empty position, or when there is a promotion in a department. This study aims to analyze the direct effect of managerial talented on work experience. This study uses a quantitative approach with a survey method by providing a list of questions to the respondent. The procedure used in testing, data processing and model development is structural equation modeling. Data were analyzed using AMOS statistical software tools. This method is used to facilitate the discovery of the effect (causal) of exogenous variables on endogenous variables. This research was conducted without any treatment from the researcher. The population in this study were all post office managers at PT. Pos Indonesia -Regional IV Jakarta, totaling 160 people. The results of this study prove that there is a positive direct effect of managerial talented on work experience.Keywords: Managerial Talented, Work Experience, Post Office.